Developing a methodology for public engagement with critical research. Issue 2 (February 2018) - Boyask, Ruth; Vigurs, Katy
In this article we argue that a refined understanding of 'public' and 'public engagement' can help researchers who produce critical research make better decisions towards achieving policy influence. We acknowledge the challenges critical researchers face in putting their research to work within the public domain. Critical research struggles to gain influence in bounded public spheres where research is valued as a consumable commodity rather than for its integrity or capacity for informing change. A starting point for developing a method of engagement is to understand better 'publics' and the different ways they may be conceptualised. We draw on a framework of three conceptualisations of the public in public engagement: bounded, normative and emergent. We use this framework to analyse our own experience of public engagement and attempts at policy influence in the Respecting Children and Young People Project. Through this analysis we recognise alternative ways to conceive of publics that may direct us away from some courses of action, and open new possibilities for public engagement with critical research.